Meditative teaching practices in chemistry teachers - HanadiYassin Amin Hassan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the light of recent developments in educational systems, teachers are required to reshape their beliefs, ideas, and methods to develop the educational process, and they also have to constantly improve their contemplative teaching practices, based on the increasing developments in education that have caught the attention of educators and to build their programs in the light of educational policy (Ryan, 2014:2). it shows the need for an educated learner to adapt to the changes that occur according to the desired goals and values and to contribute in one way or another to solving problems and meeting the needs of the learner himself and society on the other. Meditation is one of the most important modern trends for teachers , it contributes to increasing their level of motivation, increasing their willingness to teach, increasing self-confidence , understanding the challenges facing them, developing teachers ' knowledge and skills , refining classroom practice and developing decision-making skills(Pollard,2003,12-13), and demonstrating the importance of contemplative teaching practices for all teachers regardless of their level of experience, these practices have a deeper understanding of many educational issues, This helps them to make conscious decisions about these issues, especially if they are in a position of responsibility in order to move to a higher level of competence, as for junior teachers, these practices increase their understanding and awareness, instead of teaching performance based on simulation and imitation and when they reach the stage of expert teachers are properly prepared in all from professional independence, and enabling them to develop a willingness to teach they have, And critically analyze their beliefs in teaching, and increase their level of motivation. (Hafnawi and others, 7:2015).